Riscos, crises e confiança : uma análise do gerenciamento de riscos sobre segurança da informação em uma empresa brasileira de grande porte - Alves, Gilberto (2011)
For too long the quality programs and management have dominated the landscape of solutions for improving organizations. In this context, the fashions have been constant, while the consumption of many solutions. And the market seems to nurture these packages. Package on package, management in companies is being developed and specialized, and this together as the methods and techniques of good management. Risk management, specifically, is in this context. Presents itself as a management solution, but it seems to establish itself as a point of convergence and influence in the optimization and security of production processes, management and support, covering a range of possibilities in various fields of business, from finance to the aspects of fraud and daily disturbances. Following the risk management is the crisis management. This, the hemisphere of the past risks turned into real impacts with visible damage to the organization. The crisis management assumes risk management consummated and that clearly affects the organization and its context both internal and external. At the end of this logic, the trust appears as that which seals the covenant of the organization and its stakeholders as a result of good or poor risk management and crisis management. This study is, then, about risks, crises and trust and the understanding of how management overrides these elements and how it applies to organizations, specifically about a great organization of the Brazilian market. It made a research to understand the perception of employees and managers of the company studied the concepts and practices of risk management and crisis and its applications in the company. An approach is also about trust, extrapolating this concept to an idea of reliability of these practices and proposing a way to measure this reliability, identified as a gap in crisis management. In the end, an analysis is made on how to apply these concepts and practices are systematic or not, according to the hypotheses and assumptions set, verifying the character and the recent implementation of operational practices, somewhat offset from the reference model proposed for the study with little visibility on the part of employees, particularly regarding the perceived effectiveness of the practices adopted.